SOME NOTES ON RELIGIOUS RADICALIZATION AND TERRORISM IN INDONESIA - Donny Syofyan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Terrorism should not be a security issue in any part of the world anymore. It truly goes out of mainstream, namely intellectual and cultural dimensions. The dimensions are non security issues, critical education, religious depersonalization, the needs for ambassadors, reconciling liberal and fundamental Muslims and cyber religion. These dimensions constitute major aspects to be viewed when it comes to fathoming religious radicalization and terrorism across the country. Various terrorist attacks have taken place across Indonesia in the past few years. Different approaches ranging from security to cultural modes have been applied. Yet, expected outcome, which is peace, remains far from public hope. Rather than spending physical and financial resources, intellectual approach is seriously pressing. This article attempts to look into the very nature of religious radicalization leading to terrorist acts across the country Terorisme semestinya tidak lagi menjadi masalah keamanan di belahan dunia manapun. Hal tersebut berada dalam sudut pandang di luar mainstrem, yaitu dimensi intelektual dan budaya. Dimensi-dimensi tersebut di antaranya; masalah non keamanan, pendidikan kritis, depersonalisasi agama, kebutuhan akan duta besar, mendamaikan umat Islam yang liberal dan fundamental dan fenomena agama maya. Dimensi-dimensi ini merupakan aspek pembuktian utama yang harus dilihat ketika ingin memahamani radikalisasi agama dan terorisme di seluruh negeri. Berbagai serangan teroris telah terjadi di seluruh Indonesia dalam beberapa tahun terakhir. Pendekatan yang berbeda mulai dari keamanan hingga budaya telah diterapkan, namun hasil yang diharapkan, yaitu perdamaian, masih jauh dari harapan masyarakat. Daripada menghabiskan sumber daya fisik dan keuangan, akan lebih baik menekankan pendekatan intelektual secara serius. Artikel ini mencoba untuk melihat dimensi intelektual dan kebudayaan dalam mencari solusi dari dampak negatif radikalisasi agama bertolak dari pengalaman catatan-catatan tentang terorisme dan radikalisme agama di Indonesia.